Financial Performance in the Influence of Intellectual Capital and Company Size with Competitive Advantage Mediation - Sari, Mayang; Sofyaun, Ashari; Matyani, Matyani (Universitas Syiah Kuala, 2025)
The purpose of the study was to determine whether competitive advantage mediates Intellectual Capital and Company Size on financial performance. The data used were financial reports of Property and Real Estate companies on the Indonesia Stock Exchange during 2019-2023. Research findings show that Intellectual Capital has a positive effect on Financial Performance, but does not affect competitive advantage. Competitive Advantage has no effect on Financial Performance. Company Size has a positive effect on Financial Performance and Competitive Advantage. Competitive Advantage cannot mediate Intellectual Capital or company size.